Política em campo: As crônicas de João Saldanha e a consolidação do futebol brasileiro - Simões, Giulia Constante (2023)
The press in Brazil was established synchronously with our constitution as a Nation. The characters and facts remain in constant dialogue and interaction, which allowed them and still allows them to compose the processes that mark the history of our country. Football is one of those facts, disseminated and consolidated significantly through the press, arriving inBrazilian lands at the end of the 19th century as an elite sport. But it was soon appropriatedby the growing working mass and became something inseparable from Brazilian life in the first decades of the 20th century. Giving the people participation in political life, making usrepublicans in fact. A Brazilian intellectual, communicator and journalist, he stands out in the constitution of football in such a peculiar way in the country. Whether due to his personalrelationship with football or his work in the sports press, João Saldanha played a fundamentalrole in this process. It is in this context that this research is located. It is through the chroniclegenre and the Brazilian sports press that Saldanha's speech will be analyzed, which allows building and consolidating the history of Brazilian football. In this sense, the research will also allow us to go through the three main places occupied by João Saldanha, journalism, politics and football, which allow him to organize society and become a subject through football.